Accessibility and trust: the two dimensions of consumers' perception on sustainable purchase intention. Issue 2 (3rd March 2016) - Carvalho, Bárbara Leão de; Salgueiro, Maria de Fátima; Rita, Paulo
Abstract : The aim of this article is to shed new light on which dimensions compose sustainable purchase intention (SPI) with the purpose of understanding what moves consumers to a potentially more sustainable behaviour. Even though several studies have researched which factors influence consumer's intention to buy in a more sustainable way, no comparable research in consumer behaviour was found studying these dimensions in a triple bottom line perspective (profit, people, and planet) that could also provide future corporate and academic applications. Therefore, this article proposes a new construct – Consumers' Perception on SPI, defined using the C-OAR-SE procedure and measured using exploratory and confirmatory factor analysis using two different samples. In-depth interviews and online survey to actual consumers of sustainable products were undertaken in partnership with a sustainable project using its database, guaranteeing that real consumers' perceptions were gathered for this study. The construct is proposed with two dimensions (measured by nine items): Accessibility (including facets such as product lower pricing, availability in stores, and being sold within a convenient proximity to home) and Trust (including consumers needs such as: to get to know and trust products through understanding the labels; to have had good experiences in the past or simply to have new trial opportunities). Theoretical and practical implications of the findings are also discussed.